ST-51AB : study of lethal threat of damaged concrete debris due to accidental explosion - Lim, Ting Yin (2014)
This project is aimed to study the lethal threat of damaged concrete debris due to accidental explosion. It is separated into two parts. The first part will focus on the experimental procedures while the second part will be on the analysis of results obtained from all the tests. This report will cover the first part while the second part of this study will be covered by the student’s partner, Lim Lian Fei (Lim, L.F., 2014).